Inertia of the State Power Hierarchy: The Kremlin Loses Control of Regional Elites. Issue 4 (3rd July 2016) - Kynev, Alexander
Abstract : Russian regional policy in 2015 was focused on the continued dismantling of the modest political reforms introduced during the Medvedev presidency. These changes were implemented in order to minimize the possibility of the emergence and strengthening of new independent political players, and the resultant institutional imbalance toward centralization at the regional level was merely a side effect of this effort. The net effect has been a major strengthening of the power of governors at the expense of all other political actors at the regional level. The governors' power will now only be checked by federal oversight.